2016
DOI: 10.1093/bja/aev438
|View full text |Cite
|
Sign up to set email alerts
|

Cricoid pressure impedes tracheal intubation with the Pentax-AWS Airwayscope®: a prospective randomized trial

Abstract: UMIN000018209.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…This was similar to study conducted by Komasawa et al on Penatax-AWS airway scope which did not show any difference in CL grading ( P = 0.49) and POGO ( P = 0.60) with and without CP. [16] Kleine-Brueggeney et al showed the median percentile of POGO was 100 in GlideScope ® ; 90 in C MAC-D blade, Mc Grath, Airtraq, and Kingvision; 60 in A.P. Advance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was similar to study conducted by Komasawa et al on Penatax-AWS airway scope which did not show any difference in CL grading ( P = 0.49) and POGO ( P = 0.60) with and without CP. [16] Kleine-Brueggeney et al showed the median percentile of POGO was 100 in GlideScope ® ; 90 in C MAC-D blade, Mc Grath, Airtraq, and Kingvision; 60 in A.P. Advance.…”
Section: Discussionmentioning
confidence: 99%
“…[30] The increase in angle as the trachea is pushed downward during CP may exacerbate this potential problem of tube placement through glottis. [16] “Neck antiflexion” (head elevation) after laryngoscopy has been proposed to alleviate this deviation and facilitate the smooth passage of the tube. [31] At the same time, Mendonca et al did not find any significant difference in laryngoscopy time ( P = 0.020), intubation time ( P = 0.272), and success rate ( P = 0.968) with use of KVL or C MAC with the patients in neutral and sniffing position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When properly applied, CP may not affect glottic view during endotracheal intubation with either a direct laryngoscope (DL) or a video laryngoscope [46]. However, the application of CP is likely to prolong the intubation time [5, 6]. Limited mouth opening or vulnerable teeth, which often accompany the patients requiring emergency intubation, are the two common factors to deter the intubators from using a laryngoscopic device.…”
Section: Introductionmentioning
confidence: 99%